2021
DOI: 10.1093/hmg/ddab014
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent autoactivation associated with clinical variability of PDGFRB Asn666 substitutions

Abstract: Ocular pterygium-digital keloid dysplasia (OPDKD) presents in childhood with ingrowth of vascularized connective tissue on the cornea leading to severely reduced vision. Later the patients develop keloids on digits but are other ways healthy. The overgrowth in OPDKD affects body parts that typically have lower temperature than 37°C. We present evidence that OPDKD is associated with a temperature sensitive, activating substitution, p.(Asn666Tyr), in PDGFRB. Phosphorylation levels of PDGFRB and downstream target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…A child with PS and KOS overlapping features with the Asn666His variant was treated by Pond et al, with rapid improvement of contractures and decrease of coarse facial features (Pond et al, 2018). In contrast, a patient with OPDKD did not respond to imatinib treatment, despite the PDGFRB variant (Asn666Tyr) being sensitive to treatment in vivo (Bredrup et al, 2021). More recently, a patient with PS (pVal665Ala, Patient 3 on Johnston et al) was also started on imatinib, with decreased hand pain, improved skin turgor, reduction of scars, and decreased conjunctival injection, only 2 months after initiating treatment (Wenger et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A child with PS and KOS overlapping features with the Asn666His variant was treated by Pond et al, with rapid improvement of contractures and decrease of coarse facial features (Pond et al, 2018). In contrast, a patient with OPDKD did not respond to imatinib treatment, despite the PDGFRB variant (Asn666Tyr) being sensitive to treatment in vivo (Bredrup et al, 2021). More recently, a patient with PS (pVal665Ala, Patient 3 on Johnston et al) was also started on imatinib, with decreased hand pain, improved skin turgor, reduction of scars, and decreased conjunctival injection, only 2 months after initiating treatment (Wenger et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic variants in PDGFRB, either constitutional or mosaic variants, have been linked to several disorders. Loss-of-function pathogenic variants cause idiopathic basal ganglia calcification type 4 syndrome (OMIM#615007) (Johnston et al, 2015) while heterozygous germ-line activating pathogenic variants are involved in several disorders: infantile myofibromatosis (OMIM#228550; Arg561Cys, Pro660Thr, Asn666Lys, Pro560Leu, and Lys567Glu) (Arts et al, 2017;Lepelletier et al, 2017;Murray et al, 2017), PS (OMIM#601812; Val665Ala, Asn666Ser), Kosaki overgrowth syndrome (KOS) (OMIM#616592; Pro584Arg, Trp566Arg) (Gawli nski et al, 2018;Minatogawa et al, 2017), Ocularpterygium-digital keloid dysplasia (OPDKD) (Asn666Tyr) (Bredrup et al, 2021) and in a patient with a combination of PS and KOS features (Asn666His) (Pond et al, 2018). In addition, postzygotic (mosaic) activating pathogenic variants have also been described: a man with segmental overgrowth, atrophic skin and multiple intra and extracranial fusiform aneurysms (Karasozen et al, 2019) and a patient with infantile myofibromatosis and some PS and KOS-related features (Guimier et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bredrup et al recently demonstrated that the phosphorylation of STAT1, a downstream target of PDGFRB‐mediating tissue wasting, was increased at 32°C compared to 37°C in fibroblasts from patients with p.Asn666Ser Penttinen syndrome. They postulated that the increased PDGFRB‐STAT1 signaling at lower temperature peripheral body sites could explain the severe skin ulceration and tissue degenerative changes seen in Penttinen syndrome (Bredrup et al, 2021). Although speculative, this temperature sensitive activation of PDGFRB‐STAT1 signaling could offer a possible explanation for the milder phenotype seen in our patient, as the patient lives in an area with a significantly warmer climate than the other reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…This rare autosomal dominant hereditary disease is characterized by corneal vascularization leading to visual impairment early in life. Most patients also develop keloids on fingers and toes but are otherwise healthy [4][5][6]. We recently described two families presenting with OPDKD [4,6].…”
mentioning
confidence: 99%